2000
DOI: 10.1164/ajrccm.161.3.9808143
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Prospective Evaluation of Noninvasive Ventilation for Acute Respiratory Failure

Abstract: We compared noninvasive positive-pressure ventilation (NPPV), using bilevel positive airway pressure, with usual medical care (UMC) in the therapy of patients with acute respiratory failure (ARF) in a prospective, randomized trial. Patients were subgrouped according to the disease leading to ARF (chronic obstructive pulmonary disease [COPD], a non-COPD-related pulmonary process, neuromuscular disease, and status postextubation), and were then randomized to NPPV or UMC. Thirty-two patients were evaluated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(153 citation statements)
references
References 16 publications
8
135
1
9
Order By: Relevance
“…Consequently, the way of applying NIV (continuously or not) and the settings (PS and PEEP), should be questioned as it may impact outcomes. The final PS level and PEEP were 8±3 and 5±1 cmH 2 O respectively in the Florali study (10), which were similar to those in previous studies: PS between 9 to 11 cmH 2 O and PEEP 4 to 7 cmH 2 O (26,(35)(36)(37)(38)43), while NIV was continuously delivered except in the study by Hilbert et al (43). Moreover, we observed that patients with poor outcomes were more likely to generate large tidal volumes at NIV initiation than those who did not (4,5), even though PS levels did not differ (data in submission).…”
Section: Hypoxemic Arfsupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, the way of applying NIV (continuously or not) and the settings (PS and PEEP), should be questioned as it may impact outcomes. The final PS level and PEEP were 8±3 and 5±1 cmH 2 O respectively in the Florali study (10), which were similar to those in previous studies: PS between 9 to 11 cmH 2 O and PEEP 4 to 7 cmH 2 O (26,(35)(36)(37)(38)43), while NIV was continuously delivered except in the study by Hilbert et al (43). Moreover, we observed that patients with poor outcomes were more likely to generate large tidal volumes at NIV initiation than those who did not (4,5), even though PS levels did not differ (data in submission).…”
Section: Hypoxemic Arfsupporting
confidence: 86%
“…The heterogeneity of patients included in studies comparing NIV to standard oxygen, i.e., patients with hypercapnia or cardiogenic pulmonary edema, may explain high intubation rate variability (7,(35)(36)(37)(38). More recently, cohort studies including patients treated with NIV for hypoxemic ARF reported a high intubation rate, potentially exceeding 50% (39).…”
Section: Hypoxemic Arfmentioning
confidence: 99%
“…The overall efficacy of NIPPV in avoiding intubation in this study is marginally more than the rate reported in published randomised studies. 4,12 Strictly following the protocol of the study, a highly trained and motivated team of respiratory technicians along with respiratory physicians, intensivist, resident doctors, and ICU trained nurses may probably have helped to achieve the high success rate with the NIPPV. It is shown in this study that with persistence, adjustment of settings, and with change of interface in cases where indicated the overall success rate of NIPPV can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the overwhelming evidence that NPPV reduces the need for intubation, reduces mortality and complications rates, and shortens the length of stay in both the intensive care unit (ICU) and hospital (Kramer et al 1995;Brochard et al 1995;Celikel et al 1998;Martin et al 2000;Carlucci et al 2001;Mehta & Hill 2001) , NPPV should be considered as a standard of care in acute respiratory failure (ARF) due to COPD exacerbations (Keenan et al 2011). Brochard et al were the first to show that pressure-support ventilation administered via face mask significantly reduced the need for intubation, duration of mechanical ventilation, and ICU stay in patients with COPD exacerbations (Brochard et al 1990).…”
Section: Acute Respiratory Failure/exacerbation Of Copdmentioning
confidence: 99%
“…Consequently, by avoiding tracheal intubation, NPPV presents several potential advantages, such as reduction in pulmonary infections, barotrauma and need for sedation (British Thoracic Society Standards of Care Committee 2002). As a result, NPPV should be considered a standard of care to treat COPD exacerbation in selected patients, since it markedly reduces the need for intubation and improves outcome by lowering complication and mortality rates, and shortening hospital stay (Brochard et al 1995;Kramer et al 1995;Celikel et al 1998;Martin et al 2000;Conti et al 2002;Squadrone et al 2004;Lightowler et al 2003;Nava, Navalesi, & Conti 2006). Weaker evidence indicates that NPPV could allow earlier extubation, avoid reintubation in patients who fail extubation, and assist do-not-intubate patients, and thus could be beneficial for COPD patients who are suffering respiratory failure precipitated by superimposed pneumonia or postoperative complications, and COPD patients with severe stable disease who have substantial daytime hypercapnia and superimposed nocturnal hypoventilation.…”
Section: Introductionmentioning
confidence: 99%